CD44 targeted chemotherapy for co-eradication of breast cancer stem cells and cancer cells using polymeric nanoparticles of salinomycin and paclitaxel - Muntimadugu, Eameema; Kumar, Rajendra; Saladi, Shantikumar; Rafeeqi, Towseef Amin; Khan, Wahid (Colloids and surfaces, B, Biointerfaces, 2016)
[Display omitted] •Combinational chemotherapy was used to eradicate cancer cells & cancer stem cells.•Both the anticancer drugs were delivered through polymeric nanoparticles.•Paclitaxel, a conventional chemotherapeutic agent was used to kill cancer cells.•Salinomycin was selected as cancer stem cell inhibitor.•CD44 receptors on stem cells were targeted by hyaluronic acid coated nanoparticles. This combinational therapy is mainly aimed for complete eradication of tumor by killing both cancer cells and cancer stem cells. Salinomycin (SLM) was targeted towards cancer stem cells whereas paclitaxel (PTX) was used to kill cancer cells. Drug loaded poly (lactic-co-glycolic acid) nanoparticles were prepared by emulsion solvent diffusion method using cationic stabilizer. Size of the nanoparticles (below 150nm) was determined by dynamic light scattering technique and transmission electron microscopy. In vitro release study confirmed the sustained release pattern of SLM and PTX from nanoparticles more than a month. Cytotoxicity studies on MCF-7 cells revealed the toxicity potential of nanoparticles over drug solutions. Hyaluronic acid (HA) was coated onto the surface of SLM nanoparticles for targeting CD44 receptors over expressed on cancer stem cells and they showed the highest cytotoxicity with minimum IC50 on breast cancer cells. Synergistic cytotoxic effect was also observed with combination of nanoparticles. Cell uptake studies were carried out using FITC loaded nanoparticles. These particles showed improved cellular uptake over FITC solution and HA coating further enhanced the effect by 1.5 folds. CD44 binding efficiency of nanoparticles was studied by staining MDA-MB-231 cells with anti CD44 human antibody and CD44+ cells were enumerated using flow cytometry. CD44+ cell count was drastically decreased when treated with HA coated SLM nanoparticles indicating their efficiency towards cancer stem cells. Combination of HA coated SLM nanoparticles and PTX nanoparticles showed the highest cytotoxicity against CD44+ cells. Hence combinational therapy using conventional chemotherapeutic drug and cancer stem cell inhibitor could be a promising approach in overcoming cancer recurrence due to resistant cell population.